Cytarabine‐induced pericarditis confirmed using cardiac MRI: A case report. Issue 8 (29th June 2021) - Dong, Tony; Chami, Tarek; Chami, Besher; Al‐Kindi, Sadeer; Hoit, Brian D.
Abstract: Pericarditis is a rare but debilitating complication of cytarabine therapy. While echocardiography can aid with the diagnosis, cardiac MRI has superior accuracy in establishing the diagnosis. In this case, we describe a 65‐year‐old patient receiving cytarabine as part of induction chemotherapy for acute myeloid leukemia who developed acute pericarditis. Her cardiac MRI revealed pericardial edema on T2‐weighted STIR imaging and pericardial late gadolinium enhancement which confirmed the diagnosis.